A proteção de dados pessoais nas relações digitais: uma análise sob a perspectiva da teoria da eficácia horizontal dos direitos fundamentais - Santos, Isadora Beatriz Magalhães [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Modern society, driven by continuous technological advancement, has redefined and expanded the impact of personal data processing, particularly in the context of digital relationships. This dynamic process has enabled the massive use of data, intensifying power asymmetry in private relations, especially in those mediated by the internet. Personal data can be defined as a set of information capable of identifying or making a person identifiable and plays a key role in social connectivity. This occurs due to the widespread presence of platforms and services such as social networks, apps, smart devices, emails, e-commerce platforms, streaming services, digital payment systems, and digital marketing, which are increasingly integrated into the daily life of most people. In this context, surveillance and tracking of behaviors, tastes, trends, and preferences, carried out through personal data processing, emerge as a central and highly relevant issue, requiring caution, as they may pose serious risks to fundamental rights. To keep up with this technological development, many fundamental legal institutions had to undergo changes to adapt to an informational society. In this regard, with the need for regulation on personal data processing in Brazil, the General Data Protection Law (Lei nº 13.709/2018) was enacted, which, in addition to establishing rules and guidelines, highlights some fundamental rights, based on the 1988 Federal Constitution, to be applied in relationships that deal with personal data. Regarding fundamental rights and their effectiveness, the majority doctrine divides relationships into two types: vertical relationships, individuals versus the State, and horizontal relationships, between private entities. The determining difference was based on the fact that the State has the duty to guarantee rights and holds more power than private entities, justifying the classification of these relations as vertical. On the other hand, in horizontal relationships, both parties are private entities, subjects of rights, which, initially, establishes a certain equality between them, hence the term "horizontal." The debate over the possibility of applying fundamental rights in private relationships is settled in Brazil, though there are still divergences regarding the form of this applicability. In this perspective, this research aims to analyze the application of the fundamental right to personal data protection in private digital relationships, seeking a legal solution that contributes to reducing the significant power asymmetry and constant violation of fundamental rights in these relationships. To this end, a qualitative, exploratory research will be conducted using a deductive approach and a predominantly bibliographic procedure. In conclusion, it is argued that the theory of horizontal effectiveness of fundamental rights can help mitigate power asymmetry in private digital relationships, as, similarly to vertical relationships, it allows for the direct and immediate application of fundamental rights, especially when one party is a company with significant economic power.

Modern society, driven by continuous technological advancement, has redefined and expanded the impact of personal data processing, particularly in the context of digital relationships. This dynamic process has enabled the massive use of data, intensifying power asymmetry in private relations, especially in those mediated by the internet. Personal data can be defined as a set of information capable of identifying or making a person identifiable and plays a key role in social connectivity. This occurs due to the widespread presence of platforms and services such as social networks, apps, smart devices, emails, e-commerce platforms, streaming services, digital payment systems, and digital marketing, which are increasingly integrated into the daily life of most people. In this context, surveillance and tracking of behaviors, tastes, trends, and preferences, carried out through personal data processing, emerge as a central and highly relevant issue, requiring caution, as they may pose serious risks to fundamental rights. To keep up with this technological development, many fundamental legal institutions had to undergo changes to adapt to an informational society. In this regard, with the need for regulation on personal data processing in Brazil, the General Data Protection Law (Lei nº 13.709/2018) was enacted, which, in addition to establishing rules and guidelines, highlights some fundamental rights, based on the 1988 Federal Constitution, to be applied in relationships that deal with personal data. Regarding fundamental rights and their effectiveness, the majority doctrine divides relationships into two types: vertical relationships, individuals versus the State, and horizontal relationships, between private entities. The determining difference was based on the fact that the State has the duty to guarantee rights and holds more power than private entities, justifying the classification of these relations as vertical. On the other hand, in horizontal relationships, both parties are private entities, subjects of rights, which, initially, establishes a certain equality between them, hence the term "horizontal." The debate over the possibility of applying fundamental rights in private relationships is settled in Brazil, though there are still divergences regarding the form of this applicability. In this perspective, this research aims to analyze the application of the fundamental right to personal data protection in private digital relationships, seeking a legal solution that contributes to reducing the significant power asymmetry and constant violation of fundamental rights in these relationships. To this end, a qualitative, exploratory research will be conducted using a deductive approach and a predominantly bibliographic procedure. In conclusion, it is argued that the theory of horizontal effectiveness of fundamental rights can help mitigate power asymmetry in private digital relationships, as, similarly to vertical relationships, it allows for the direct and immediate application of fundamental rights, especially when one party is a company with significant economic power.
The Protection of Personal Data in Digital Relations: A Study Based on the Theory of the Horizontal Applicability of Fundamental Rights.
Keywords: Proteção de dados pessoais; Eficácia Horizontal; Direitos fundamentais; Relações digitais